The spectres of biography: archive as artwork - Partridge, Matthew Duke (My University, 2014)
In an attempt to understand the multiple lives of an object - specifically a death inquest register from the year 1976 - this dissertation examines five moments in the objects life (referred to as the Ledger) that invest it with ‘capital’. They are; • The Cillié Commission of Inquiry. • Sam Nzima’s photograph of Hector Pieterson. • The destruction of apartheid documents in the early 1990’s. • Kendell Geers’ appropriation of the Ledger. • Museum Africa’s purchase of the Ledger. By applying a biographical methodology to this object, this dissertation examines how the shifts in the multiple lives of the Ledger address the different roles that the archive plays in the construction of memory in South Africa.
Keywords: Archives in art.; Art, South African.; Art--South Africa--Exhibitions.